Cities, people & the economy : a study on positioning Penang (Kuala Lumpur, Malaysia Khazanah Nasional, 2010)
This book is an output of the 'positioning Penang' study, a collaborative research project between Khazanah Nasional Berhad and The World Bank, identified by the Economic Planning Unit (EPU) as one of the inputs to the tenth Malaysia Plan. This book, which primarily targets policy makers, draws on a strong body of empirical work conducted in a dozen technical background papers contributed by a team of internationally-renowned researchers and field practitioners of the Malaysian economy. The book proposes a multidimensional growth strategy which embraces three elements: cities, people and the economy. At present, these elements are out of phase with each other in Penang. The urban cycle is just starting to enter a recovery phase, following the World Heritage designation of George Town. The people cycle is still in a recession, with new graduates choosing to leave the area. The economy is caught in a slump, with the boom years a thing of the past. Implementing a coherent strategy across these areas, cities, people, and the economy, could lead to a sustainable, inclusive and rapid development that benefits not just Penang and its environs in the Northern corridor, but the nation as a whole. The book suggests some levers of change and contributes inputs to the preparation of the tenth Malaysia five-year plan.
"A collaborative research between Khazanah Nasional, The World Bank."
Includes bibliographical references (p. 91-92).
Also available online.
Keywords: Economic development projects -- Malaysia -- Pinang; Pinang -- Economic conditions; Pinang -- Economic policy